Asupan Zat Gizi Makro, Aktivitas Fisik dan Tingkat Stress dengan Kejadian Hipertensi pada Dewasa (18-60 Tahun) - Erlyta Windi Mulyasari; Mia Srimiati (Jurnal Ilmiah Kesehatan (JIKA), 2020)
Based on the results of Health Research in 2013, the prevalence of hypertension in Indonesia at the adults of >18 years were 25,8%. West java is the fifth largest province with the highest prevalence of hypertension of 29,4%. Based on data from Departement of Health of Depok City (2016), hypertension is a disease that many people in Depok City experience. This research aimed to Analyze the correlation between macro nutrition intake, physical activity and levels of stress with event of hypertension in the Depok City. The research with cross sectional study design in 80 people by using purposive sampling. Macro nutrition intake was obtained from interview of food recall 1x24 hours, physical activity was obtained using International Physical Activity Questionnare (IPAQ), and stress level was obtained using Perceived Stress Scale (PSS). The correlation test of this study used spearman ordinal. The result showed that there was no significant relationship between carbohydrate intake. There were significant correlations between protein intake, fat intake, physical activity and stress level with event of hypertension. The older a person is, the higher the risk of suffering from hypertension.